Performance Practice in a Pandemic: Training Ensemble Skills Using E-Tivities in Music Teacher Education - Karkina, Svetlana; Faizrakhmanova, Lyalya; Kamalova, Ilmira; Akbarova, Gulnaz; Kaur, Balwinder (Frontiers in Education, 2022)
The emergency situation in pandemic due to the spread of virus COVID19 has brought new requirements to educational conditions in Higher Education in order to manage the learning process. In the musical ensemble class, performance practice is mandatory and has a crucial role in musical education. Shifting this class in the online environment required the implementation of a new type of student-teacher interaction such as e-tivity. It is a dynamic and interactive learning process led by a teacher in an online way. The investigation of the efficiency of e-tivity for training musical ensemble skills was carried out in the paper. The research was tested through the experimental work which had taken place at Kazan Federal University (Russian Federation). Due to the complete shift of the education process totally in a distance way, all disciplines were studied online, including the specific musical courses that required collective work with face-to-face interaction. The curriculum of future music teachers includes an ensemble basic course to train students` musical performance skills in groups. The work in the classes of instrumental and vocal ensembles gathered 114 students and was organized by the means of e-tivity based on several online tools, including Aiseesoft Video Converter Ultimate. This tool allows creating the video with a split-screen effect. By using such a tool students created the video to follow the teacher`s instruction separately and afterward, they united their musical records in one video with a split-screen effect. At the end of the research work musical artworks belonging to the following art styles: classical, Tatar and Russian folk music, and jazz were collected. The analysis of the obtained data exhibited a high level of results in each criterion scale and effectiveness of the online work with musical ensembles which covered educational activity irrespective of the emergency. Students witnessed improvement in self-education by the means of creativity and critical self-assessment. The increasing frequency of students` listening of their own performance during the ensemble music-making by e-tivity brought advantages for the involuntary repetition process.